NUMERICAL SIMULATION AND OPTIMIZATION OF MICRO‐IRRIGATION FLOW REGULATORS BASED ON FSI1. (21st July 2013) - Lili, Zhangzhong; Peiling, Yang; Shumei, Ren; Dan, Wu
ABSTRACT The micro‐irrigation flow regulator markedly improved the uniformity of micro‐irrigation systems by adjusting flow with internal elastomers. Meanwhile, the relatively wide flow path and the ability to self‐clean ensure the high anti‐clogging performance of the regulators and reduce clogging risk in the irrigation system. Hence the ability to work under various pressures or poor water supply conditions became the advantage of the micro‐irrigation flow regulator. In this paper, a large eddy simulation (LES) model was established to simulate the fluid–structure interaction (FSI) of micro‐irrigation flow regulators, and its feasibility was proven through a hydraulic performance experiment. The internal flow fields and elastomers were then studied and optimized by adopting this model. The results showed that for the internal elastomer, maximal displacement of the elastic diaphragm occurred in the centre of the circle. When the elastic diaphragm thickness or elastic modulus decreased, the flow regime indexes declined as a whole. Such a decrement indicated performance improvement of the flow regulators. But when both the thickness and elastic modulus of elastic diaphragm reach their minimums (0.3 mm and 3.0 MPa), the diaphragm itself started to oscillate, or drop dramatically in area of flow cross‐section, due to oversized deformation, resulting in deterioration of irrigation uniformity. As for the flow path, its energy dissipation effect was significantly improved by adopting the fractal flow path for optimization.Finally, a new micro‐irrigation flow regulator (tooth tine angle of fractal flow path: 60°, thickness of elastomer: 0.3 mm, elastic modulus of elastomer: 3.5 MPa) was designed, and its flow regime index was reduced to 0.08, representing a good and steady performance in flow regulation. Copyright © 2013 John Wiley & Sons, Ltd.